Structural applications and emerging trends of nano- and biocomposites: a review - Md. Sazib Mollik, Sazib; Hasan, Muhammad Hasibul; IRUM Tariq, Irum (Trans Tech Publications Ltd., Switzerland, 2015)
Composite materials are currently being used in applications for aerospace, leisure, construction, sport, packaging and automotive industries, especially for the last mentioned application.Yet, present day trends such as a rise in interest in environmentally-friendly materials and the advancement of nanotechnology has led to the emergence of nano- and biocomposites. These materials offer comparable mechanical properties to conventional composites, with biocomposites having the added benefit of being biodegradable. This paper explores the nano- and biocomposites, focussing additionally on structural applications and emerging trends of this growing market.